Penggunaan Media Instagram @Arabiyahtalk Dalam Maharah Kitabah Mahasiswa Bahasa Arab - Eliya Qori’ah, Evi; M. Abdul; Rahmadani (Shaut al Arabiyyah, 2023)
This study aims to open new innovations in online learning in Maharah Kitabah learning for Arabic students. Instagram, which has been only for posting photos, stories and videos of interesting and unique benefits, has been created, effectively used as a learning medium for the Mahārah Kitabah. Shows a positive response from students towards the use of Instagram media. Researchers focus on using the Instagram account @Arabiyahtalks which contains mufrodzat, uslub and Qowaid Nahwu. The research method uses descriptive qualitative, with data collection through observation, interviews and documentation. The results showed that the Instagram @Arabiyahtalks media account was very interesting and the material posted was very easy to understand, so students were motivated and it was easier to hone learning. Students gave positive responses because they were flexible, not limited by time, learning was more varied and students were more active and creative. As for the negative responses, students need an internet connection, the teacher does not control it directly. Researchers hope that with this research, teachers can use the Instagram application as a medium for learning Arabic, so that students can wisely use social media.